Review articlesCannabinoid receptor agonists in topical anti-pruritic and anti-inflammatory therapy - Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Itching sensation is a common dermatological problem accompanying various inflammatory skin diseases. Usually it is related to the complicated interactions between the immunological and nervous system with various cytokines, neuropeptides and other signalling molecules being involved. Apart from treatment of the underlying skin disease, effective anti-pruritic therapy is absolutely necessary because the itching sensation significantly reduces the quality of life of the patients. Topical cannabinoid agonists seem to be an effective new alternative for treating chronic pruritus. Physiogel A.I.® contains N-palmitoylethanolamide (PEA) belonging to the family of N-acylethanolamines. Via their cannabinomimetic action these substances present analgesic, antioxidant, anti-inflammatory and anti- pruritic characteristics. It has also been suggested that PEA might suppress UV-induced skin photodamage. Results of clinical trials conducted in order to investigate the anti-pruritic and anti-inflammatory effect of PEA containing Physiogel A.I.® cream in patients with atopic dermatitis and other pruritic skin diseases showed substantial reduction of skin pruritus and inflammation. In patients suffering from atopic dermatitis decline of loss of sleep and reduced use of topical corticosteroids have been recorded.